Application of waste chalk/CoFe2O4/K2CO3 composite as a reclaimable catalyst for biodiesel generation from sunflower oil. (February 2022) - Foroutan, Rauf; Peighambardoust, Seyed Jamaleddin; Mohammadi, Reza; Peighambardoust, Seyed Hadi; Ramavandi, Bahman
Abstract: This investigation aimed to produce a new composited catalyst from a waste chalk powder, a waste generated by the construction industry, to produce biodiesel from sunflower oil. The waste chalk was modified by CoFe2 O4 nanoparticles and K2 CO3 . The surface tests showed that the obtained catalyst has been successfully synthesized with desired surface properties. The surface areas of waste chalk, waste chalk/CoFe2 O4, and waste chalk/CoFe2 O4 /K2 CO3 were determined 20.8, 77.8, and 5.8 m 2 /g, respectively. This indicates that the waste chalk/CoFe2 O4 /K2 CO3 catalyst has a lower surface area due to K2 CO3 being placed on the catalyst. Results showed the efficiency of RSM-CCD (R 2 = 0.992) compared to ANN (R 2 = 0.974). It was shown that a contact time of 180 min, a temperature of 65 °C, a waste chalk/CoFe2 O4 /K2 CO3 mass of 2 wt%, and methanol to oil mole ratio of 15:1 gave the highest efficiency (98.87%) of biodiesel production at the laboratory conditions. The kinetic results of the process showed the energy of activation and frequency factor of 11.8 kJ/mol and 0.78 min −1, respectively. Also, the values of ΔH°, ΔS°, and ΔG° at 65 °C was calculated to be 9010.7 J/mol, −256.3 J/mol and 95.7 kJ/mol, respectively, indicating that the biodiesel production process is endothermic requiring high energy for proceeding. The generated catalyst has an efficiency of over 90% up to 6 steps of reuse. The generated biodiesel was met most of the international standard levels. Graphical abstract: Image 1 Highlights: A catalyst was prepared from waste chalk waste and its structure was modified. Waste chalk/CoFe2 O4 /K2 CO3 was used to produce biodiesel from oil sunflower. The BET of waste chalk/CoFe2 O4 /K2 CO3 were 5.8 m 2 /g. The catalyst had a good efficiency for biodiesel production up to 6 stages. Ea (11.8 kJ/mol) and frequency factor (0.78 min −1 ) of the process was obtained.